Carbon microspheres supported cobalt catalysts for phenol oxidation with peroxymonosulfate - Zhou, G.; Zhou, L.; Sun, Hongqi; Ang, H.; Tadé, M.; Wang, Shaobin 222090D (Institution of Chemical Engineers, 2015)
Heterogeneous catalytic oxidation of organic pollutants has been widely applied for wastewater treatment, in which the development of highly efficient catalysts is of critical importance. In this study, carbon microspheres supported cobalt catalysts (Co/CS) were prepared by a one-pot hydrothermal method for in-situ loading cobalt onto carbon spheres, followed by calcination at 300, 400 and 500 °C, respectively. Cobalt would distribute three-dimensionally in the spheres. Many characterization techniques, such as XRD, SEM, EDS and elemental mapping were applied to investigate the physicochemical properties of the supported catalysts. The catalytic activities were evaluated by decomposition of phenol solutions with sulfate radicals. It was found that the Co/CS catalysts were able to efficiently decompose phenol by activation of peroxymonosulfate (PMS). Co/CS-300, 400 and 500 can completely decompose 20 ppm phenol in 15, 5 and 10 min, respectively. Kinetics studies were carried out to investigate the effects of catalyst loading, PMS amount, and reaction temperature on phenol degradation efficiency.